Effect of five-membered sugar mimics on mammalian glycogen-degrading enzymes and various glucosidases. - Minami, Y; Kuriyama, C; Ikeda, K; Kato, A; Takebayashi, K; Adachi, I; Fleet, G; Kettawan, A; Okamoto, T; Asano, N (2008)
We investigated inhibitory activities of five-membered sugar mimics toward glycogen-degrading enzymes and a variety of glucosidases. 1,4-Dideoxy-1,4-imino-D-arabinitol (D-AB1) is known to be a potent inhibitor of glycogen phosphorylase. However, the structural modification of D-AB1, such as its enantiomerization, epimerization at C-2 and/or C-3, introduction of a substituent to C-1, and replacement of the ring nitrogen by sulfur, markedly lowered or abolished its inhibition toward the enzyme. The present work elucidated that d-AB1 was also a good inhibitor of the de-branching enzyme of glycogen, amylo-1,6-glucosidase, with a IC(50) value of 8.4 microM. In the present work, the de-sulfonated derivative of salacinol was isolated from the roots of Salacia oblonga and found to be a potent inhibitor of rat intestinal isomaltase with an IC(50) value of 0.64 microM. On the other hand, salacinol showed a much more potent inhibitory activity toward maltase in Caco-2 cell model system than its de-sulfonated derivative, with an IC(50) value of 0.5 microM, and was further a stronger inhibitor of human lysosomal alpha-glucosidase than the derivative (IC(50)=0.34 microM). This indicates that the sulfate in the side chain plays an important role in the specificity of enzyme inhibition.